Medium‐term effects of active management on the structure of mature Douglas‐fir (Pseudotsuga menziesii) stands. Issue 8 (21st August 2019) - Williams, Neil; Powers, Matthew
Abstract: We developed an observational study to (1) examine differences in the structure of mature Douglas‐fir stands representing thinned, structural retention harvest and unmanaged conditions, and (2) assess the extent to which active management in mature stands expedites development of old‐growth structure, relative to two old‐growth indices. Time since treatment averaged 38 and 22 yr in thinned and retention harvest conditions, respectively, and stand age ranged from 106 to 193 yr when sampled. Differences in stand structure were apparent between all three management conditions, with attributes associated with stumps, live tree diameter diversity, understory vegetation, and vertical foliage structure being the strongest individual drivers of these differences. Mean old‐growth index scores were lower than expected of true old‐growth for each of the management conditions examined here, but were not significantly different between thinned and unmanaged stands. Our results suggest thinning in mature stands may promote certain elements of old‐growth structure, including foliage height diversity, but also indicate the need for provisions against the depletion of dead wood resources. Stumps are an understudied dead wood structure, and in actively managed mature stands, our results imply that stumps may provide a degree of functional substitution where down log availability is low.